2016
DOI: 10.1021/acs.iecr.6b01573
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Surface Engineering of Polystyrene Beads Used to Challenge Automated Particle Inspection Systems

Abstract: Container challenge sets, used in the qualification and validation of automated visible particle inspection systems in the parenteral drug industry, are prepared by seeding a single standardized polystyrene-divinylbenzene (PS-DVB) bead inside the commercial product to mimic foreign particulates. Due to its low surface energy and wettability, the bead adheres to container walls, hindering its detection by the motion based inspection system. The aim of this research is to modify the surface properties of the bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Previously, our group studied the chemistry of syngas photo-initiated chemical vapor deposition (PICVD) on flat surfaces 40 , 41 , 52 and on particulates in a plug-flow configuration 42 , 53 55 . Herein, we adapt this process for use in a sub-pilot scale jet-assisted fluidized bed reactor (FB-PICVD) to coat large quantities of MIONPs (grams) in order to improve their dispersion and stability in non-polar (hydrophobic) media.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our group studied the chemistry of syngas photo-initiated chemical vapor deposition (PICVD) on flat surfaces 40 , 41 , 52 and on particulates in a plug-flow configuration 42 , 53 55 . Herein, we adapt this process for use in a sub-pilot scale jet-assisted fluidized bed reactor (FB-PICVD) to coat large quantities of MIONPs (grams) in order to improve their dispersion and stability in non-polar (hydrophobic) media.…”
Section: Introductionmentioning
confidence: 99%
“…Very few researchers have attempted to study the photopolymerization of syngas components, 9,35 and most have focused on carbon monoxide photochemical reactions in the early Earth's atmosphere or with low wavelength VUV lamps. [35][36][37] Previously, our group demonstrated that syngas PICVD could be used to deposit thin films with various functionalities on copper substrates 9 and nanomaterials, [38][39][40][41] but the deposition mechanism and kinetics remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Also, pluronic micelles could concentrate the proteins at the particle surface and the stability and bioactivity of the proteins are higher than the aqueous phase 47. Polystyrene beads are also proposed to be safest particles for protein adsorption 48. Liposomes are reported as good proteins carriers because of their size, aqueous core, biocompatibility and biologically inertness, weak immunogenic nature, and limited toxicity that protect peptides in the GI 49,50.…”
Section: New Drug Delivery Systems For Peptidesmentioning
confidence: 99%